Effect of auxin types on in vitro and ex vitro rooting and acclimatization of grapevine as influenced by substrates - Barreto, M. S.; Nookaraju, A. (Indian Journal of Horticulture, 2007)
Transferring micropropagated plantlets from in vitro to in vivo conditions is a critical step because plantlets have under-developed cuticle and stomata which result in wilting due to low humidity, fungal attack and bleaching in high light intensities. The resumption of terminal growth indicates successful establishment which is a change from mixotrophy to autotrophy. The survival of Vitis vinifera cvs. 2A-Clone and Red Globe plantlets rooted in vitro was 86.66 and 83.33%, respectively and the established plants showed a well-defined root system. Plantlets rooted in vivo by auxin pulse were easier to transfer and acclimatize with a survival percentage of 96.66 and 79.92 for 2A-Clone and Red Globe, respectively but the rooting was of fibrous type with few main roots and less number of root hairs. Coco-peat in combination with sand and soil was better for quick acclimatization and establishment (97.5 and 95% survival for 2A-Clone and Red Globe respectively) of the micropropagated plantlets.
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Synergistic effect of CPPU and benzyladenine on embryo rescue in six. stenospermocarpic cultivars of grapevine - Nookaraju, A.; Barreto, M. S.; Karibasappa, G. S.; Agrawal, Dinesh C. (Vitis, 2007)
In ovulo/embryo culture technique has been used to recover hybrids from seedless grapevines. The present investigation was carried out to study the influence of pre-bloom sprays of N-(2-chloro-4-pyridyl)-N'-phenylurea (CPPU) - a synthetic cytokinin, and N-6-benzyladenine (BA) supplemented in culture media on embryo recovery in six stenospermocarpic grapevine cultivars. The results showed synergistic effect of CPPU and BA on embryo recovery. Though a CPPU spray alone increased embryo recovery in four out of six cultivars tested, the efficiency was enhanced several fold on culture of excised ovules on media supplemented with BA. The percentage of embryo recovery also depended on BA concentration and varied among six cultivars indicating a genotypic influence as well. Germination percentage of rescued embryos varied among the six cultivars and mostly corresponded with embryo recovery. Germinated embryos developed into normal plantlets. Present study demonstrates that spraying of panicles with CPPU and incorporation of BA in the ovule culture medium can enhance the embryo recovery in stenospermocarpic cultivars of grapevine.
Keywords: benzyladenine; CPPU; embryo rescue; seedless grapes

Variability among vitis vinifera cultivars to in vitro propagation - Barreto, M. S.; Nookaraju, A.; Joglekar, A. M.; Karibasappa, G. S.; Agrawal, Dinesh C. (Proceedings of the International Symposium on Grape Production and Processing, 2008)
Response of grapevines to tissue culture has been reported to be genotype dependent, hence it becomes imperative to optimize culture conditions for newly developed varieties or cultivars, needing a large scale planting but availability of sufficient planting stock is a constraint. In the present study, conditions for in vitro propagation of six popular table grape cultivars have been standardized. Single node stem segments of cultivars 2A-Clone of Thompson Seedless, Red Globe, Crimson Seedless, Thompson Seedless, Flame Seedless and Italia cultured on ten different basal media showed varied percentages of bud break and morphogenetic responses. The percentage of bud break varied among the six cultivars. Direct rooting at basal ends of single node segments was observed in all the cultivars except in Italia. Woody plant medium induced the highest response and Eriksson medium the least in all the cultivars tested. Rooted nodal segments with shoots in axils could be established into whole plants on potting. Six cultivars showed different optimum concentrations of growth regulators for induction of maximum number of multiple shoots in both primary as well as secondary nodal segments. Shoot proliferation could be enhanced by several fold in the majority of cultivars on culture of initial shoot clumps to glass bottles instead of culture tubes. Six cultivars showed significant differences in optimum requirement of nutrients and growth regulators for shoot elongation, in vitro and ex vitro rooting and survival rate. Tissue culture plants of all the six cultivars could establish successfully in a greenhouse.
Keywords: basal media; Grapevine; growth regulators; micropropagation; Tissue culture; Vitis

Genetic homogeneity of in vitro raised plants of grapevine cv. crimson seedless revealed by ISSR and microsatellite markers - Nookaraju, A.; Agrawal, Dinesh C. (South African Journal of Botany, 2012)
The present study was conducted to test the clonal homogeneity of six month old tissue culture raised plants of grapevine cv. Crimson Seedless using Inter Simple Sequence Repeat (ISSR) and Simple Sequence Repeat (SSR) markers. Visible assessment of these in vitro raised plants maintained in polyhouse did not show any morphological differences among themselves. However, to test the genetic homogeneity of these plants, we screened 50 ISSR primers out of which, 22 primers produced scorable and repeatable bands. These 22 primers were used further for assessing genetic homogeneity of in vitro raised plants of Crimson Seedless. These 22 ISSR primers generated 134 distinct band classes with a total of 3216 scorable bands. All the primers showed uniform banding pattern for all the in vitro raised plants and the mother plant. In case of 5 SSR primers (VS I, VVMD5, VVS2, VMCNG4c8 and VVMD31) used, a total of 288 scorable bands were obtained. The allele sizes ranged from 98 to 254 bp. Allelic composition of 23 in vitro raised plants and the mother plant at 5 SSR loci did not show any polymorphism. The results of the two marker systems in the present study revealed the genetic uniformity among the in vitro raised plants demonstrating the reliability of in vitro propagation system used for the cultivar. (C) 2011 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Allele composition; Clonal fidelity; Inter Simple Sequence Repeats; Monomorphic bands; Tissue culture; Vitis vinifera L.

Use of amino acids for a highly efficient somatic embryogenesis in grapevine `Crimson Seedless' - Nookaraju, A.; Agrawal, Dinesh C. (Vitis, 2013)
Somatic embryogenesis influenced by growth regulators and amino acids was studied in in vitro leaves of grapevine `Crimson Seedless'. In vitro leaves of the cultivar were collected from multiple shoot cultures maintained on Murashige and Skoog's (MS) basal medium supplemented with 9 mu M N-6-benzyladenine (BA). Among the growth regulators used, BA at 4.5 mu M induced higher embryogenic response producing more number of somatic embryos per explant. This response was increased with the addition of 5 mu M naphthoxyl-acetic acid (NOA) to 1/2 MS containing 4.5 mu M BA. Further, supplementation of amino acids in the callus induction medium significantly improved the embryogenic response of in vitro leaves. The higher number of explants showing somatic embryo production (55.3 %) and higher number of somatic embryos per explant (15.5 per explant) were recorded with the supplementation of 5 mM phenylalanine to callus induction medium. Primary somatic embryos showed repetitive embryogenesis on % MS medium devoid of growth regulators. Plantlets derived from somatic embryos were transferred to soil-sand-peat mixture (1:1:1 v/v) and hardened plantlets were established in greenhouse with 90 % survival. This somatic embryogenesis system has been successfully used for Agrobacterium-mediated transformation studies in `Crimson Seedless' in our laboratory. To our knowledge, this is the first report on the use of amino acids for the high efficient somatic embryogenesis in grapevine.
Keywords: Amino acids; somatic embryogenesis; Vitis vinifera L.; `Crimson Seedless'